Adaptive and Digital Marketing: A Sustainable Strategy for Developing Culinary SME Business (Law of the Republic of Indonesia. Number 20 of 2008) Post-Pandemic - Rini Rahayu Kurniati; Fitri Hidayat (International Journal of Artificial Intelligence Research, 2022)
When situations and conditions in the small, medium and large-scale environments change, these changes have an impact on every activity, even the most pronounced post-pandemic areas of business. The SME-class culinary business in the city of Batu can survive and some are growing in the pandemic situation and conditions, and this is an interest to be researched to develop a post-pandemic business. This study uses a qualitative type with data collection namely observation, interviews, and documentation then analyzed using an interactive model. The results of this study prove that the Adaptive Strategy (SA) contributes to providing solutions to survive and or develop, it should be noted that being adaptive requires various maturity steps by examining various internal and external aspects. At least it needs a concept or strategy of "landscape, learning, leadership", which is strengthened by considerations and policies in efficiency, utilization, flexibility, timeliness, value, or cost. So that it can increase the ability to survive and even develop in various situations. In addition to Adaptive Strategies, Culinary SMEs use digital marketing strategies through social media. Social media is effective for business activities because it can bring together a brand/company/business with the target audience/market. Thus increasing revenue and being able to grow the business.